Easy and Convenient Presentation of Information Modern Method - Guzal Malikova (Genius Journals, 2023)
This article talks about infographics, its structure, types and features. The reason is that infographics are useful in attracting the attention of the general public to information material even in the direction of news delivery today. It helps in covering events related to various areas of society and reflecting its results.
Keywords: Infographic; visualization; diagram; timeline